Identities in transition : the pursuit of Isa. 52:13-53:12 - Joachimsen, Kristin (Leiden ; Boston : Brill, 2011)
Isa. 52:13-53:12 has occupied a special position within Jewish and Christian traditions, as well as within biblical scholarship. This book focuses particularly on different ways of reading this text. Historical-critical readings in the tradition after Bernhard Duhm are challenged. In Duhmian readings of Isa. 52:13-53:12, Gottesknecht has become a technical term, Ebed-Jahwe-Lied a genre, Stellvertretung an established theological concept and "servant song research" a separate discipline within biblical scholarship. After a critical presentation of the Duhmian readings, three other ways of reading Isa. 52:13-53:12 based on variations of linguistic theory are presented: one linguistic, one narratological and one intertextual. These show in different manners how the text is unstable, heterogeneous and composite. In these readings, the trope of personification is central.
Based on the author's doctoral thesis, University of Oslo, 2006.
Includes bibliographical references (p. [397]-419) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc